Hajj Implementation Policy in Indonesia - Wibowo, Hendro; Mubarok, Abdullah (Indo Consultan Energi, 2024)
Indonesia has the largest Muslim population in the world and the most significant number of Hajj pilgrims, reaching 15-25% of the total number of Hajj pilgrims in Arab Studies. The government's primary concern is the implementation of Hajj. This study aims to identify the policy of implementing Hajj in Indonesia. This study uses a qualitative method with a descriptive approach and a literature study. Data were obtained from journal literature, books, and policy documents on implementing Hajj in Indonesia. The results of the study found that the policy of implementing Hajj in Indonesia includes macro, meso, and micro dimensions in the form of Laws, Government Regulations, Presidential Regulations/Presidential Decrees, Regulations of the Minister of Religion, Decrees of the Minister of Religion, and Governor's Decrees. The government and stakeholders organizing Hajj need to use these policies as a reference when implementing Hajj.